Predicting response to CGRP-monoclonal antibodies in patients with migraine in Japan: a single-centre retrospective observational study - Keiko Ihara; Seiya Ohtani; Narumi Watanabe; Nobuyuki Takahashi; Naoki Miyazaki; Kei Ishizuchi; Satoko Hori; Ryo Takemura; Jin Nakahara; Tsubasa Takizawa (The Journal of Headache and Pain, 2023)
Abstract Background Anti-calcitonin gene-related peptide monoclonal antibodies (CGRPmAbs) are a favourable option for patients with migraine who experience distressful headache disability and fail to respond to traditional preventive treatment options. However, since CGRPmAb has been available for only 2 years in Japan, the difference between good and poor responders remains unknown. We aimed to investigate the clinical characteristics of patients with migraine in Japan who responded well to CGRPmAb based on real-world data. Methods We analysed patients who visited Keio University Hospital, Tokyo, Japan, between the 12th of August 2021 and 31st of August 2022, and were prescribed one of three CGRPmAbs (erenumab, galcanezumab, and fremanezumab) for more than 3 months. We recorded the patients’ basic migraine characteristics, such as pain quality, monthly migraine days (MMD)/monthly headache days (MHD), and the number of prior treatment failures. We defined good responders as patients whose MMDs decreased by more than 50% after 3 months of treatment and other patients as poor responders. We compared the baseline migraine characteristics between the two groups and performed logistic regression analysis based on the items that showed statistically significant differences. Results In total, 101 patients were considered eligible for the responder analysis (galcanezumab: 57 (56%), fremanezumab: 31 (31%), and erenumab: 13 (13%)). After 3 months of treatment, 55 (54%) patients achieved ≥ 50% reduction in MMDs. Comparisons between ≥ 50% responders and non-responders revealed that age was significantly higher (p = 0.003), and MHD and total prior treatment failures were significantly lower (p = 0.027, 0.040, respectively), in responders than in non-responders. Age was a positive predictive factor, and the total number of prior treatment failures and past medical history of immuno-rheumatologic diseases were negative predictive factors of CGRPmAb responsiveness in Japanese patients with migraine. Conclusions Patients with migraine who are older, with fewer prior treatment failures and no past history of immuno-rheumatologic disease, may respond well to CGRPmAbs.